Kompetensi kewirausahaan pribadi dan semangat kewirausahaan mahasiswa di Jember - Tamriatin Hidayah; Hary Sulaksono (STIE Perbanas Surabaya, 2015)
Entrepreneurship education will be integrated into the education system has the potential to support economic growth. Sector of entrepreneur should start to grow, not only for the general public, but also among the students. On the other side, there were many differences in the Personal Entrepreneurial Competency (PEC) among students between state univer-sities and private universities. Target of research was description potency and intention of student in private university and state university. The purpose of study were: (1) Identify PEC and entrepreneurial intentions of students on state and private universities in Jember; (2) Identify the factors driving and inhibiting the development of an entrepreneurial cul-ture in state and private universities in Jember. The research method using the PEC and Intention Entrepreneurship. Results: Internal Push Factors identified in the role of Univer-sities. Internal Inhibiting Factors identified as the weak role of the Universities, while inhi-biting factors external, public perception that the entrepreneurial future is uncertain. From the results of the mapping of potential entrepreneurial ability, most of the students in the state and private universities in Jember on various items in the position enough ratings or moderate. Entrepreneurship intention is influenced by Openness to experience, Self Effica-cy, Subjective Norm, Traits, where each variable is different effects in Universities.